Combating child obesity: impact of HENRY on parenting and family lifestyle. Issue 5 (2nd July 2013) - Willis, T. A.; George, J.; Hunt, C.; Roberts, K. P. J.; Evans, C. E. L.; Brown, R. E.; Rudolf, M. C. J.
Summary What is already known about this subject The rise in child obesity poses a serious public health challenge. It has been argued that efforts may be best targeted towards prevention, but there is a relative dearth of initiatives targeting infants. Earlier evaluation of the impact of HENRY (Health Exercise Nutrition for the Really Young) has shown an improvement in the way practitioners work with families and a positive impact upon their work setting and personal life. What this study adds This study of the impact on families found that parents participating in HENRY groups report a healthier family lifestyle, which was sustained at follow‐up. Participants reported increased parental self‐efficacy around lifestyle change and parenting generally. They also reported increased consumption of fruit and vegetables; positive changes in mealtime behaviours and reduced screen time. Background One‐quarter of children in England are overweight/obese at school entry. We investigated the impact of a programme designed to provide parents of infants and preschool children with the skills required for a healthier family lifestyle. Method A cohort of families was followed across the 8‐week HENRY (Health Exercise Nutrition for the Really Young) parent course at nine locations in England. Seventy‐seven parents enrolled on the course, of which 71 agreed to complete questionnaires addressing eating behaviours, dietary intake and parental self‐efficacy. Pre‐ and post‐course data was available from 60 (84.5%) parents (8‐week follow‐up data from 58 parents) and was analysed using repeated measures analyses. Results Significant changes were observed, with most sustained at follow‐up. Parents reported increased self‐efficacy and ability to encourage good behaviour (P < 0.001). Increased consumption of fruits and vegetables was reported in both children and adults, together with reduced consumption of sweets, cakes and fizzy drinks in adults (all P < 0.01). There were also positive changes in eating behaviours (e.g. frequency of family mealtimes and eating while watching television or in response to negative emotion [P < 0.01] ) and reduced screen time in adults (P < 0.001). Discussion The results build upon earlier evaluation, indicating that the HENRY intervention has a beneficial impact upon the families of infants and preschool children. Furthermore, the findings suggest that positive changes inspired by the programme can be maintained beyond its completion. Such changes may serve to protect against later obesity.